Anticipated Ramsey reforms and the uniform taxation principle: the role of international financial markets - Stephanie Schmitt-Grohé; Martín Uribe (European Central Bank (ECB), 2003)
This paper studies the role of asset-market completeness for the properties of optimal fiscal and monetary policy. A suitable framework for this purpose is the small open economy with complete international asset markets. For in this environment changes in policy represent country-specific risk diversifiable in world markets. Our main finding is that the fundamental public finance principle whereby when taxes on all final goods are available, it is optimal to tax final goods uniformly fails to obtain. In general, uniform taxation is optimal because it amounts to a non-distorting tax on fixed factors of production. In the open economy this principle fails because when households can insure against the risk of a policy reform, initial private asset holdings are contingent on actual policy and thus no longer represent an inelastically supplied source of income. Furthermore optimal consumption and income taxes do not respond to government purchases shocks and the Friedman rule is optimal only if the Ramsey planner has access to consumption taxes.
Keywords: F41; E52; E61; E63; 330